Introduction : la crise des études stratégiques - David, Charles-Philippe (Études internationales, 1989)
The young field of strategic studies has difficulties establishing a solid consensus on its purpose, basic philosophy and main concepts, because the definitions and meanings given to the nature of research in that field are largely controversial. Strategists have serious problems in addressing the criticisms that are made of the fundamental assumptions and theories that underline strategic studies. This paper explores the causes and implications of a crisis which now permeates heavily the development of the field.